The Effect of Tax Planning and Company Size on Earning Management (Study on Pharmaceutical Subsector Companies on the Indonesia Stock Exchange) (International Journal of Scientific Research and Management (IJSRM), 2023)
This study aims to determine the effect of tax planning and company size on earnings management in pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange in 2020-2021. The research method used is descriptive method. The sampling technique used purpopsive sampling so that the number of samples obtained was 16 companies. The analysis technique used is multiple regression analysis. The results show that partially tax planning has a positive effect on earnings management, it can be seen from the results of the t test or partial test, that the significance value of tax planning is 0.024 less than 0.05. And the size of the company has a significant positive effect, it can be seen from the results of the t test or partial test, that the significance value of tax planning is 0.032 less than 0.05. Simultaneous test results show that tax planning and company size affect earnings management in pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange in 2020-2021, this is indicated by the value of Fcount > Ftable with a value of sig 0.009 < 0.05.